PREVENTING CAPITAL MARKET VIOLATIONS AND CRIMES IN THE CONTEXT OF THE SELFREGULATORY ORGANIZATION FUNCTION - Mrs. Sulistyowati; Mr. Paripurna (Fakultas Hukum Universitas Gadjah Mada, 2014)
This study examines the preventive measures that can be taken by the Indonesian Stock Exchange (IDX) in their capacity as an SRO in response to capital market infractions. The main role of IDX is as a provider of facilities and infrastructure in capital market activities. Nonetheless, as a self- regulatory organization (SRO) IDX has additional role as regulator of the capital markets with limited authority. This study found that IDX was quite consistent in upholding the legislation in the field of capital markets. However, compliance level of the exchange members is still quite low. Penelitian ini meneliti langkah-langkah pencegahan pelanggaran dan kejahatan pasar modal yang dapat diambil oleh BEI dalam kapasitasnya sebagai SRO. Peran utama BEI adalah sebagai penyedia sarana dan prasarana dalam kegiatan kepasarmodalan. Meskipun demikian, sebagai self-regulatory organization(SRO) BEI mempunyai peran tambahan sebagai regulator pasar modal dengan kewenangan terbatas dalam menetapkan peraturan. Penelitian ini menemukan bahwa BEI telah cukup konsisten dalam menegakkan peraturan perundang-undangan di bidang pasar modal. Akan tetapi tingkat kepatuhan anggota bursa dapat dikatakan masih cukup rendah.